REGIONAL AND ETHNIC VALUES, LANGUAGE AS A KEY FACTOR OF PRESERVING NATIONAL IDENTITY OF ETHNIC GROUPS, BASED ON THE TRADITIONS OF WESTERN GEORGIA – MARRIAGE - DUMBADZE, Sopiko; LORIA, Manuchar (Humanities and Social Sciences, 2025)
Ajara, a region in Georgia, is famous for its traditions and culture. The article explores the traditions of the Ajarian people that have mostly faded with time but still remain in some parts of Ajara. The work provides information about the marriage traditions and rituals of the Ajarians and the set of lexical units connected to that group of people, which are at risk unless they are documented. The paper aims to record them; it will be a treasure depicting and preserving the Ajarian cultural heritage. It can contribute to the creation of the ethnolinguistic dictionary. The dictionary will help to make the lexical units set in stone that may become the point of interest for future researchers and generally for linguists. The work will raise awareness about this ethnic group worldwide. It will enhance the popularization of national culture. The complex research methodology was applied in the study. The empirical method, the method of analysing scientific literature and the field research contributed a lot. Significant data were collected through observations and semi-structured interviews. This article, consequently, plays a considerable role in archiving specific elements from the history, culture, and language of the Ajarians.